Doxycycline in Extremely Low Dose Improves Glycemic Control and Islet Morphology in Mice Fed a High-Fat Diet - Chen Y (Dove Medical Press, 2021)
Yixin Chen,1 Yu Chen,2 Na Wang,2 Shanhong Gu,1 Meilin Wang,1 Yucai Fu,3 Chiju Wei,2 Wencan Xu1 1Department of Endocrinology, The First Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong, 515041, People’s Republic of China; 2Laboratory of Molecular Biology, Multidisciplinary Research Center, Shantou University, Shantou, Guangdong, 515063, People’s Republic of China; 3Laboratory of Cell Senescence, Shantou University Medical College, Shantou, Guangdong, 515041, People’s Republic of ChinaCorrespondence: Chiju WeiShantou University, 243 Daxue Road, Shantou, Guangdong, 515063, People’s Republic of ChinaEmail chijuwei@stu.edu.cnWencan XuDepartment of Endocrinology, The First Affiliated Hospital of Shantou University Medical College, 57 Changping Road, Shantou, Guangdong, 515041, People’s Republic of ChinaEmail xuwcan@163.comPurpose: Chronic low-grade inflammation is detected in obese and diabetic individuals. Tetracyclines, used as antibiotics for years, have been demonstrated to have diverse non-bactericidal effects, including anti-tumor and anti-inflammatory activities. This study aimed to investigate whether doxycycline at sub-antimicrobial concentrations could improve glycemic control in mice fed a high-fat diet, through its anti-inflammatory activities.Methods: C57BL/6J mice were fed with a high-fat diet to induce diabetic and obese conditions. Three sub-antimicrobial dosages of doxycycline (200, 20, and 2 μg/mL) were added to drinking water for 23 weeks during the housing phase.Results: Doxycycline at 200 μg/mL tended to increase body weight, islet mass, and the percentage of large islets (diameter > 350 μm). At 20 μg/mL, doxycycline significantly improved glucose tolerance and decreased fasting blood glucose. At 2 μg/mL, doxycycline increased the percentage of small islets (diameter < 80 μm). Serum C-reactive protein and lipopolysaccharide levels significantly decreased while the beta-cell ratio increased in all doxycycline-administered mice.Conclusion: Our results suggest that doxycycline, even at an extremely low dose, could improve glycemic control and islet morphology via its anti-inflammatory activities.Keywords: doxycycline, inflammation, T2DM, diabetes, glucose metabolism